THU0239 IDENTIFICATION OF BIOMARKERS AND IMMUNE PATHWAYS FOR PERSONALIZED DRUG TARGETING IN PATIENTS WITH NEWLY DIAGNOSED PRIMARY SJÖGREN'S SYNDROME. (June 2019) - Verstappen, Gwenny M.; Gao, Lu; Pringle, Sarah A.; Terpstra, Janneke H.; Liefers, Silvia C.; van Nimwegen, Jolien F.; Vissink, Arjan; Patel, Vishal; He, Aiqing; Truong, Amy; Hu, Sarah; Dongre, Ashok; et al.
Abstract : Background: Patients with primary Sjögren's syndrome (pSS) present with heterogeneous clinical symptoms and immune dysregulation. How immune dysregulation in SS arises is poorly understood, which hampers development of effective therapies. Identification of key immune pathways contributing to pSS pathogenesis is essential for successful drug development. Systemic treatment of patients early in the disease process will limit irreversible damage to salivary and lacrimal glands, as well as to other affected tissues. Objectives: To identify early systemic biomarkers and dysregulated immune pathways in newly diagnosed pSS patients by multidimensional immuno-profiling. Methods: We included 40 newly diagnosed pSS patients (39 female; mean age 51±14) and 20 age- and sex-matched non-SS sicca patients (19 female; mean age 50±13). All pSS patients fulfilled ACR-EULAR criteria. Serum and peripheral blood mononuclear cells (PBMC) were collected and cryopreserved. PBMCs were thawed for immunophenotyping by flow cytometry and RNA isolation. RNA sequencing was performed using TruSeq Stranded Total RNA Library Prep Gold (Illumina), following manufacturer's recommendations, and RNAseq libraries were sequenced on a HiSeq2500 system. Additionally, serum proteomics and immunoassays for pro-inflammatory cytokines in serum were performed. Results: Interferon (IFN) type I signaling pathways were at the top of enriched pathways in PBMCs from pSS patients, compared with non-SS sicca controls (adjusted p<0.05). Additionally, the gene signature of IgD - CD27 - CXCR5 - CD11c + (double negative 2; DN2) B cells was significantly upregulated in pSS patients (adj. p<0.05). Immunophenotyping analysis showed increased frequencies of CD40 + pDCs (p=0.004), intermediate monocytes (p=0.008), ICOS + memory CD4 + T cells (p<0.001), cTfh cells (p=0.001), and cTfr cells (p<0.001) in pSS patients. Memory B cells were significantly decreased in pSS patients (p<0.001). Serum proteomics showed that the top proteins up-regulated in pSS patients were immunoglobulin subunits. The top of up-regulated pathways involved IFN signaling (adj. p<0.05), similar to RNAseq data. Consistently, immunoassays showed increased levels of CXCL10 in serum and MxA in whole blood of pSS patients, compared with non-SS sicca controls (p=0.009 and p=0.001, respectively). Blood MxA protein levels correlated strongly with the IFN signature score in PBMCs (Rs=0.8; p=10 -12 ). The T cell-related biomarkers described above, the frequency of memory B cells, and MxA levels correlated significantly with EULAR Sjögren's disease activity index (ESSDAI) scores, whereas the frequency of CD40 + pDCs, intermediate monocytes, and serum CXCL10 levels did not correlate with these scores. When a correction for multiple testing was applied, only cTfr cells correlated significantly with ESSDAI scores (Rs=0.5; p=0.002). Conclusion: Newly diagnosed patients with pSS show co-activation of the IFN type I and B cell activation pathways, compared to non-SS sicca controls. At the same time, CD4 + T cell subsets critical for B cell function are activated, which can enhance B cell activation and plasma cell formation. Personalized treatment based on the activity of each pathway in individual patients potentially increases the efficacy of such treatments. Acknowledgement: Part of this work was funded by NIH grant RFA-DE-06-004 Disclosure of Interests: Gwenny M. Verstappen: None declared, Lu Gao Employee of: Bristol-Myers Squibb, Sarah A. Pringle: None declared, Janneke H. Terpstra: None declared, Silvia C. Liefers: None declared, Jolien F. van Nimwegen Speakers bureau: Bristol-Myers Squibb, Arjan Vissink: None declared, Vishal Patel Employee of: Bristol-Myers Squibb, Aiqing He Employee of: Bristol-Myers Squibb, Amy Truong Employee of: Bristol-Myers Squibb, Sarah Hu Employee of: Bristol-Myers Squibb, Ashok Dongre Employee of: Bristol-Myers Squibb, Arathi Krishnakumar Employee of: Bristol-Myers Squibb, Stefan Kirov Employee of: Bristol-Myers Squibb, Julie Carman Employee of: Bristol-Myers Squibb, Hendrika Bootsma Grant/research support from: Unrestricted grants from Bristol-Myers Squibb and Roche, Consultant for: Roche, Bristol-Myers Squibb, Novartis, Medimmune, Union Chimique Belge, Speakers bureau: Bristol-Myers Squibb, Novartis, Frans G.M. Kroese Grant/research support from: Unrestricted grant from Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Roche, Janssen-Cilag